A New Method to Pair‐match Metacarpals Using Bilateral Asymmetry and Shape Analysis1. Issue 1 (23rd July 2014) - Garrido‐Varas, Claudia; Rathnasinghe, Raveen; Thompson, Tim; Savriama, Yoland
Abstract Matching pairs of skeletal elements is of fundamental importance when re‐associating skeletons from commingled settings. This study presents a new method that combines the use of traditional anthropometric size measurements and the analysis of shape, through geometric morphometrics, to form pairs from commingled settings. We tested the hypothesis that shape asymmetry among individuals is smaller than between individuals that share similar dimensions. The metacarpals were measured in their maximum length, and absolute means of asymmetry between right and left metacarpals were calculated. To analyze the shape characteristics, two‐dimensional landmarks were recorded from digital images of 111 metacarpals. The specimens were analyzed using generalized Procrustes analysis and multivariate statistics. The accuracy of pair‐matching bones using a combined method was of 100%, showing that the incorporation of geometric morphometrics techniques—in the assessment of shape in physical anthropology—is of particular use when comparing the shape differences/similarities between individuals.